Macrocyclis peruvianus (Gastropoda, Acavidae), an endemic land snail from Chile - Silva,Leticia F. da (2009)
Macrocyclis peruvianus (Lamarck, 1822) is a large terrestrial snail which is endemic in Chile. A detailed description of its shell structure, jaw, radula, palial cavity and reproductive system is presented here for the first time.